Dimensions of Readiness for Change Seen from the Role of Workplace Well-Being - Endah Andriani Pratiwi; Rafika Ayu Masputri (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to determine and analyze the effect of Workplace Well-Being on Readiness for Change in employees. The approach used is quantitative with a causality research type, in order to test the causal relationship between variables. The research design is non-experimental with an inductive approach. Data collection was carried out by distributing questionnaires to 122 permanent employees of PT X who are active and have not yet approached retirement, which is less than 3 years. The sampling technique uses a non-probability sampling method. The measurement instrument used is the Workplace Well-Being Index (WWBI) with a Likert scale as a measure of respondent perception. Data analysis was carried out using simple linear regression to see the magnitude of the influence of the independent variables on the dependent variable. The results showed that Workplace Well-Being has a positive and significant effect on Readiness for Change, with a contribution of 50.8%. This study also identified several supporting factors such as age, gender, length of service, educational background, and psychological resources as elements that influence individual readiness to respond to organizational change.